2005
DOI: 10.1021/ef040064l
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Plug Prevention by Quaternary Ammonium Salts

Abstract: The use of low-dosage inhibitors is an alternative to thermodynamic inhibitors to prevent gas hydrates from plugging oil production pipelines. In this work, quaternary ammonium salts (QAs) with different structures were tested as hydrate plug inhibitors on model systems containing 1/1/4/X proportions (by weight) of water/THF/oil/QA systems. The experimental results suggest that the presence of both small (CH3) groups in their polar moiety and two long alkyl chains in their hydrophobic part has a beneficial eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 16 publications
(18 reference statements)
6
108
1
Order By: Relevance
“…Arquad 2HT is a hydrophobic quaternary ammonium surfactant, and surfactants with this chemistry have been found to be much more effective as inhibitors. 8,15 It was thought that a better understanding of how surfactants like these affect capillary forces from water bridges between hydrophilic particles in a nonaqueous medium may provide some insight into how hydrate inhibitors prevent the adhesion of hydrate particles. Figure 8 shows the effects of various concentrations of Span 80 on the dispersion viscosity.…”
Section: Methodsmentioning
confidence: 99%
“…Arquad 2HT is a hydrophobic quaternary ammonium surfactant, and surfactants with this chemistry have been found to be much more effective as inhibitors. 8,15 It was thought that a better understanding of how surfactants like these affect capillary forces from water bridges between hydrophilic particles in a nonaqueous medium may provide some insight into how hydrate inhibitors prevent the adhesion of hydrate particles. Figure 8 shows the effects of various concentrations of Span 80 on the dispersion viscosity.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, the formation of water-in-oil emulsions has been proposed as a requirement for hydrate anti-agglomeration [11,16,[18][19][20]. However, the AA proposed in this work is effective in an oil-free system.…”
Section: Analysis Of the Aa's Anti-agglomeration Mechanismsmentioning
confidence: 99%
“…In the 1980s, the French Petroleum Institute confirmed that nonionic amphiphilic surfactants can effectively inhibit gas hydrate from generating [13][14][15]. Subsequently, Shell found that the quaternary ammonium surfactant was an ideal agglomeration inhibitor and argued that two or more n-butyl, n-pentyl or isopentyl ammonium salts had a good performance of delaying hydrate crystal growth [16]. In addition, the BJ UnichemCompany found that quaternized polyamine polyethers are more efficient than polyvinyl caprolactam (PVCap) and some quaternary anti-agglomerants in preventing the accumulation of tetrahydrofuran hydrate [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, thermodynamic inhibitors or low dosage hydrate inhibitors, such as kinetic inhibitors (KIs) and anti-agglomerants (AAs) [1][2][3][4], are injected to inhibit or control the formation of hydrates. On the other hand, hydrate slurry might become an alternative approach for oil and gas transportation, as large amounts of natural gas can be stored in the form of hydrates.…”
Section: Introductionmentioning
confidence: 99%